Study Optical Properties of (GA) Polysaccharide/Polyvinyl alcohol thin films - Mohanad Qader Kareem (Tikrit Journal of Pure Science, 2023)
In this research a new Thin films from mixing together natural polymer  (Gum acacia) polysaccharide with artificial polymer ( polyvinyl alcohol ) have been prepared using cast method .Optical absorption spectra of these thin films have been recorded  in the wavelength range (200-900)nm using UV-spectrophotometer .With thickness (3μm) the Optical band gap of the films has been calculated by using Taucs  relation and variations in the values of optical band gap with the variation of concentrations in the blend films have been found from (3.75 -4.1) eV.